ANALISIS DISTRAKTOR INSTRUMEN UJIAN AKHIR SEMESTER MATA PELAJARAN MATEMATIKA KELAS VII MTS SE-KECAMATAN KEDIRI DENGAN MENGGUNAKAN PROGRAM ITEMAN - Taufik, Ahmad; Suryadi, Hendra (LPPM Institut Pendidikan Nusantara Global, 2023)
One of the educational evaluation tools is a test with the aim of measuring the success of the learning activity process. When compiling tests/questions, they must be prepared in accordance with the rules for compiling them so that they will provide maximum information regarding the results of learning activities to obtain good tests both after and before use. Mathematics teachers at the KKM (Madrasah Working Group) have never carried out an analysis of the distractors for the final exam questions for the 2022/2023 academic year that they have prepared and used, so the quality of the questions is not yet known. The problem is how the quality of the questions is seen from the distractors in the multiple choice questions. Thus, this research aims to determine the distractors in the questions based on students' answers to 30 multiple choice questions with 4 alternative answers, namely (A, B, C and D) which were tested in class VII MTs at the KKM level in Kediri sub-district for the 2022 school year. /2023 with data and documentation of 369 students. This research is descriptive research, with quantitative and qualitative approaches. The results of the analysis with the Iteman program showed that there were 20 questions whose alternatives worked, namely questions 1, 3, 4, 6, 8, 9, 10, 12, 13, 14, 17, 18, 19, 20, 22, 23, 24, 27 , 29, 30. The other alternative answer questions are classified as revised, namely 2, 5, 7, 11, 15, 16, 21, 25, 26, 28. So it can be concluded that the distractors of the 30 multiple choice questions are based on student answer documentation data as many as 369 students, it can be seen that 10 or 43% of the answer choices have not functioned well. Therefore, it is necessary to revise the questions qualitatively on the distractors to get good distractors/distractors.